(untitled) - T.-N. Chang; T.-N. Chang (Singapore,River Edge, N.J., 1993)
Detailed discussions on many of the recent advances in the many-body theory of atomic structure are presented by the leading experts around the world on their respective specialized approaches. Emphasis is given to the photoionization dominated by the resonance structures, which reveals the effect of the multi-electron interaction in atomic transitions involving highly correlated atomic systems. Recent experimental developments, stimulated by the more advanced applications of intense lasers and short wavelength synchrotron radiation, are also reviewed. This book brings together a comprehensive theoretical and experimental survey of the current understanding of the basic physical process involved in atomic processes
Includes bibliographical references
Keywords: Many-body problem; Photoionization; Atomic structure